Caracterização de ambientes com ocorrência natural Acrocomia aculeata (Jacq.) Lodd. ex Mart e suas populações nas regiões Centro e Sul do Estado de Goiás - TELES, Heria de Freitas (2009)
In the Cerrado, some species of palm trees stand out from the natural, economic, and ecological point of view, either by the predominance, either by exuberance of the plant or importance in the wild fauna and/or flora equilibrium, or even by use of their products and byproducts by the local community. Among these, the macauba (Acrocomia aculeata) occurs in abundance in some states, mainly in Goiás. Increasingly this palm has aroused interest, by its high production of fruits and several uses, such as food, forage, ornamental and oilseed production. And, furthermore, its fruits are highly prized for human consumption, domestic and wild fauna. However, the existing exploitation is basically extractivist and with low productivity. The installation of commercial fields lives together with a series of difficulties, including the lack of knowledge of its ecological requirements. This research aimed to characterize environments of naturally occurring macauba and their respective populations, in the regions Center and South of the State of Goias. Ten areas were studied, located in seven municipalities: Santa Cruz de Goiás, São Miguel do Passa Quatro, São Francisco de Goiás, Parauna, Jandaia, Indiara and Jaraguá. Soil chemical and physical characterizations were carried out, in addition to the description of a brief topossequence description. Climatic data relating to historical series from 1961 to 1990 were obtained, as well as a biometric survey of plants and fruits. According to results, the species occurs in greater density in soils of medium to high fertility. Areas with a predominance of Cambisolos and Neossolos, and with medium texture or sandy clay loam, presented higher plant density. Greater concentration of macauba plants occurs in portions of convex slope, talus and concave slope of topossequences. The macauba develops in soils with base saturation above 50% and high levels of potassium, as evidenced by the presence of muscovite in the areas of occurrence. There is phenotypical variability of the characters studied between plants of macauba of different areas and, in particular, between plants within the area. The population of macauba in the municipality of Jamaica is more productive in terms of number of bunches per plant. Macauba presents both phenologic stages of flowering and fructification, besides bunches of fruit in different stages of development, producing around three to five bunches of fruits per plant in the regions Center and South of the State of Goias. There is no correlation between biometric data of plants and soil fertility variables. Biometric data of fruits have variation between areas, between plants within the area and, mainly, between fruits in trees. The micronutrient iron in the soil is positively correlated with almond average mass and calcium is negatively correlated with number of almonds. The average mass of fruit is positively correlated with across and longitudinal diameters and with the total almond mass. In general, the fruit of macauba presents one to three almonds and is constituted of 23.73% of shell, 33.10% of endocarp, 34.28% of pulp and 8.89% of almond.